The spatiotemporal variable effects of individuals’ CO2 emission in Bandung Metropolitan Areas - Dimas B.E. Dharmowijoyo; Cynthia D. Maharani (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2022)
Many investigations have been using disaggregated measurements to estimate individuals' CO2 from road passenger transport, especially in developed countries. Nevertheless, similar investigation in developing countries emphasized their focus on aggregate measurements and system dynamics. There is a lack of disaggregated measurement in developing countries, particularly in Indonesia, and how the effects of spatiotemporal variables such as socio-demographic, travel parameters, and activity pattern variables correspond with CO2 estimations. Since Indonesia is dominated by motorcycle users, this study will show motorcycles' contribution to CO2 emissions. The results of 2.23 kg-CO2 per day of individuals’ CO2 emissions in Indonesia is quite low in comparison to results in some developed countries such as the Netherlands and Sweden. It is presumably because around 86.05% of individuals in the observations used private motorcycles to travel and a low number of the undertaken trip in the BMA (Bandung Metropolitan Area). Around 91.39% of CO2 emissions were emitted by individuals who take 80% of using private motorcycles and cars. This study shows that the disaggregated modeling on estimating CO2 emissions might be able to reveal which individuals can be targeted to reduce their CO2 emissions and what can be done to help government policy in reducing CO2. Female part-timer workers, female non-workers, and senior citizens are those who show the lowest contributions to CO2, and providing acknowledgments might make them keep such achievements. Whose daily travel time is below 106 and 125 minutes might be clustered as the targeted group of individuals that can reduce their CO2 production. Incentive schemes such as providing internet vouchers or vouchers to use ride-hailing might help to change their habits to shift some of their trips by taking non-motorized mode, public transport, and/or ride-hailing services. Keeping public amenities at a farther distance might reduce people increase trips and travels by using motorized mode. But increasing the distance might make effects social exclusion, in turn, social health.